Diretrizes curriculares nacionais para o curso de psicologia : aproximações e distanciamentos dos projetos pedagógicos de curso - Fenerich, Maria Elisa de Agostini (2015)
Considering the DCN a major public policy for training the Psychologist in health, and structuring the curriculum, this study aimed to analyze the pedagogical projects of undergraduate courses in Psychology of public higher education institutions in the state of São Paulo by the DCN. As methodological course, it was a kind of interpretative-explanatory study of a qualitative nature. The educational projects of the six study target schools were obtained by means of a documentary collection, and subsequently were treated through a documentary analysis. From an agreement between researchers from the Post-Graduation Program in the UFSCar Clinic Management was built a matrix as a methodological tool containing two axes: Curricular Axis and Professional Profile Axis and, from these, the analysis categories were defined: C1-Curricular organization: most courses are organized according to the rules of DCN, however, traditional curriculum models are still present; C2- Learning conceptions: more than half of the courses guided their curricula in teachinglearning process proposed by the DCN, and some of these still have more innovative experiences. Other courses present traditional learning conceptions and distant from the DCN; C3- Student assessment procedures: the student assessment envisaged by the DCN is not well defined, as in the case of half of the courses. P1 General Profile; most courses include somehow the professional profile recommended by DCN; P2- Attention and Health Care: two courses are distant from health care benchmarks and model of care proposed by the DCN, and, two stand out due to their larger focus. P3- Health Management: most of the courses, as well as DCN, don’t have a clear delineation of management processes; P4- Health education: the DCN and the courses do not explicitly show this category, except in one of these. Data analysis shows the similarities and differences of pedagogical projects of the courses by DCN about the categories, as well as their intentions. The results indicate the current state of the curricula and training of Psychology for health, and the need for changes both in DCN as in the courses curricular development and reform.